Progress in controlling the transmission of schistosome parasites in Southern Ethiopia: the Geshiyaro Project in the Wolaita Zone - Birhan Mengistu; Ewnetu Firdawek Liyew; Melkie Chernet; Geremew Tasew; Santiago Rayment Gomez; Rosie Maddren; Benjamin Collyer; Ufaysa Anjulo; Adugna Tamiru; Kathryn Forbes; Zelalem Mehari; Kebede Deribe; et al. (Parasites & Vectors, 2024)
Abstract Background This paper describes changes in the prevalence and intensity of schistosome parasite infections in a project integrating mass drug administration (MDA), water, sanitation, and hygiene (WaSH), and behavioral change interventions. Methods The Geshiyaro Project comprises three intervention arms. Arm 1 is subdivided into “Arm 1 pilot” (one district) and Arm 1 (four other districts), both receiving integrated community-wide MDA with intensive WaSH interventions. Arm 2 involves 17 districts with community-wide MDA interventions, while Arm 3 serves as a control with school-based MDA interventions in three districts. A total of 150 individuals, stratified by age group, were randomly selected from each of the 45 sentinel sites. Arm sizes were 584 (Arm 1 pilot), 1636 (Arm 1), 2203 (Arm 2), and 2238 (Arm 3). Statistical tests were employed to compare infection prevalence and intensity across the different arms. Results The prevalence of schistosome parasite infection ranged from 0% to 2.6% and from 1.7% to 25.7% across districts, employing the Kato-Katz (KK) and point-of-care circulating cathodic antigen (POC-CCA) diagnostics, respectively. The mean infection intensity level showed no marked difference between baseline and follow-up surveys when measured by KK, except in Arm 2 (t = 6.89, P < 0.0001). Infection prevalence decreased significantly in Arm 1 (t = 8.62, P < 0.0001), Arm 2 (t = 6.94, P < 0.0001), and Arm 3 (t = 8.83, P < 0.0001), but not in Arm 1 pilot (t = 1.69, P = 0.09) by POC-CCA, when trace was considered positive. The decrease was significant only in Arm 1 (t = 3.28, P = 0.0001) and Arm 2 (t = 7.62, P < 0.0001) when the trace was considered negative in POC-CCA. Arm 2 demonstrated a significant difference in difference (DID) compared to the control group, Arm 3, regardless of whether trace in POC-CCA was considered positive (DID = 3.9%, df = 8780, P = 0.025) or negative (DID = −5.2, df = 8780, P = 0.0004). Conclusions The prevalence of schistosomiasis was low when employing the KK diagnostic but moderate in some locations by the POC-CCA diagnostic. The infection level had decreased across all arms of the Geshiyaro study at mid-term of the 7-year project, but further efforts are needed to reduce the rate of parasite transmission based on the POC-CCA diagnostic scores. Graphical Abstract